Using Artificial Intelligencein the Field of Intelligence Operations and Analysis - Daricili, Ali Burak; El-Bayaa, Nourhan (CRC Press, 2024)
The nature of intelligence activities has been changing. With these technological advances, newsgathering and analysis methods have been diversified and become more effective. There is a tremendous development process in intelligence technologies. New-generation technological capabilities contribute immensely to the implementation of intelligence activities and increase the efficiency. The new-generation technological developments have a great impact on intelligence collection and analysis methods. It can be claimed that artificial intelligence (AI) algorithms, models, and software are at the forefront among the new-generation technological developments that most affect the nature of intelligence activities. In this context, this study analyzes the impact of AI algorithms and models on intelligence collection and analysis in various aspects. © 2025 selection and editorial matter, Mehmet Emin Erendor; individual chapters, the contributors.